Uso de medicamentos en gestantes con infección urinaria mediante el seguimiento farmacoterapéutico atendidas en el Hospital Regional de Loreto 2021 - Zevallos Capillo, Diana Maria (2022)
The purpose of this study was to determine the problem related to medications in pregnant women diagnosed with urinary infection at the Regional Hospital of Loreto, year 2021, the methodology was prospective, descriptive and longitudinal, the sample consisted of 50 pregnant women who presented UTI; the pharmacotherapeutic follow-up sheet and the results of the urine culture samples were applied; the results in sociodemographic characteristics was 44.0% between 26 and 30 years; 76.0% from the district of Iquitos; 58.0% with higher education. The results of the physical examination related to urine were density 88.0%; pH 77.0%; cloudy at 100.0%. Chemical tests such as urobilinogen, blood and ketone bodies were 100.0% negative; in nitrites and proteins it was positive. Microscopic examinations of epithelial cells and urea were 100.0% normal, while leukocytes were not 100.0% normal; in red blood cells 58.0%, in creatinine 64.0% and 78.0% in glucose presented normal values. In urine culture samples, germs such as E. Coli were found in 94.0% and after pharmacotherapeutic follow-up the reduction was 22.0%. The problem related to medications according to categories: need 50.0%; effectiveness 22.0%; and security 28.0%. Conclusion, the proper use of medications for urinary tract infection was carried out through Pharmacotherapeutic Follow-up and urine culture, in pregnant women treated at the Regional Hospital of Loreto 2021.